Accountıng choıces under ıfrs and theır effects on banks’ fınancıal statement comparabılıty: empırıcal comparatıve study of Turkey and the uk - Aljakhlab, Darwısh Mostafa (My University, 2016)
Bu araştırma bankacılık sektöründe IFRS’de mevcut olan muhasebe seçeneklerinin finansal tabloların karşılaştırılmasıyla ilgili etkilerini incelemektedir. IFRS’de mevcut olan tüm seçenekler belirlenmiş ve düzenlenmiştir. 2012 yılına ait banke konsolide finansal tablolar ve bağımsız denetim raporları Borsa İstanbul ve Londra Menkul Kıymetler Borsalarının listelerinden alınmıştır. Uygulanan muhasebe alternatifleri her banka için belirlenmiştir. Muhasebe seçeneklerinin finansal tabloları nasıl etkiledikleri ve bankaların aynı olay karşısında hangi muhasebe seçeneklerini tercih ettikleri ile ilgili nitel bir çalışma kullanılmıştır. Taplin (2004) tarafından geliştirilmiş olan T-index modelini, Borsa İstanbul ve Londra Menkul Kıymetler Borsasında bankaların finansal tablolarının hem ayrı ve hem de birlikte olarak karşılaştırılması için kullanılmıştır. Sonuçlar 20 muhasebe seçeneğinin finansal tablo tutarlarında belirgin şekilde değişiklik yaptığını ve 16 seçeneğin önemli bir etkisinin olduğunu ortaya çıkarmıştır. Bazı özel durumlar için borsaya kote bankalar farklı muhasebe alternatifleri kullanmışlardır. Muhasebe alternatifleri arasinda karşılaştırma sevıyesine belırlemede üç değişık kategoride ele alınmıştır; tam karşılaştırılabilir, kısmen karşılaştırılabilir ve karşılaştırılamaz. Borsa İstanbul’a kote bankaların finansal tabloları Londra Borsası’ndakBorsası’ndakilere oranla daha kıyaslanabilir. Dolayısla ülke içinde kıyaslama ülkeler arası kıyaslamadan daha sağlıklı sonuçlar vermektedir. Sonuç olarak, aynı sektörde olsun ya da olmasın IFRS çoklu muhasebe alternatifleri finansal tabloların tamamıyla kıyaslanmasını sağlar. IFRS, Muhasebe Seçenekleri, Muhasebe Politikaları, Finansal Tablolar, Karşılaştırılabilirlik, Tekdüze Muhasebe, Esnek Muhasebe.

This research examines the effects of accounting choices available in IFRS on financial statement comparability, particularly in the banking industry. All accounting choices under IFRS are determined and organized. Consolidated financial statements together with independent auditor's reports for the year 2012 are collected for listed banks in Borsa Istanbul and the London Stock Exchange. Applied accounting alternatives for every bank are identified. A qualitative approach is used to explore how accounting choices influence financial statements and to what extent listed banks select identical accounting alternatives for the same event. A quantitative approach is used to test the differences between accounting alternatives under every accounting choice. The T-index model, developed by Taplin (2004), is used to measure the comparability of listed banks’ financial statements in BIST and LSE, both separately and together. The findings reveal that 20 accounting choices have significantly changed financial statement amounts and 16 choices have an insignificant effect. For some specific events, listed banks chose different accounting alternatives. The results of measuring the comparability level between accounting alternatives show three alternative categories; fully comparable, fractionally comparable, and completely non-comparable alternatives. BIST listed banks’ financial statements are more comparable than LSE listed banks’ financial statements, consequently, comparability levels within countries is healthier than the comparability across countries. Finally, permitting multiple accounting alternatives in IFRS makes full financial statement comparability, either in the same industry, or within or across countries, unachievable at present. IFRS, Accounting Choices, Accounting Policies, Financial Statements, Comparability, Uniformity accounting, Flexible accounting.
Keywords: İşletme; Muhasebe; Yönetim